TINDAK PIDANA LINGKUNGAN HIDUP DALAM KAITANNYA DENGAN PEMANFAATAN ENERGI NUKLIR - Petrus Avelino Framayuka Tolang; Geradin Mayella Jivisina Kotan; Unchianus Natalius Tety Nahak (Jurisprudentie: Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2020)
ABSTRACTThe development of technology in the world lately is very rapid, nuclear technology is widely applied in various fields. By utilizing nuclear energy, humans get huge benefits. The use of nuclear technology is also not spared from accidents. Nuclear accidents are caused by too much energy which is often very dangerous. In relation to nuclear issues with the legal consequences of the use of nuclear technology and environmental criminal liability.This research uses a normative juridical approach that is descriptive in nature with existing literature and regulatory studies relating to the environment and nuclear.The use of nuclear energy cannot be separated from the consequences of the law. due to the law in the form of a nuclear accident that causes a loss originating from radiation or combined radiation. This has an impact on the environment in the form of damage that has a negative effect on humans and ecosystems in general. Related to the legal consequences caused, it should be held liable according to law which in this case is criminally. In nuclear accidents related to the environment, individuals and corporations may be held liable for criminal penalties in accordance with the PPLH Law in the form of basic criminal penalties for individuals and also corporations or legal entities with principal penalties in the form of criminal fines and additional penalties in the form of confiscation of evidence, compensation, compensation, restitution, repair of damage resulting from criminal acts. The handling of this corporation is clarified by the Supreme Court Regulation of the Republic of Indonesia Number 13 of 2016 concerning Procedures for Handling Criminal Acts by Corporations due to obscurity in the criminalization of corporations in the PPLH Law. As for punishment as a result of nuclear utilization which has an impact on the environment its nature is ultimum remedium or as a final remedy.Keywords: Nuclear Utilization, Nuclear Accidents, Criminal Liability.